DIUBER (elastic sleeve pads) / Mohd Izwan Nasir - Nasir, Mohd Izwan (Universiti Teknologi MARA, Kedah, 2018)
"DIUBER" is the name of sportwear product for volleyball sport. This "DIUBER" target user focusing for volleyball player especially at beginner level. It is because of the product helps and improve hand posture technique when doing training. The materials using in this product is magnet on both of thumb and there are a few of elastic rubber at elbow area. Lycra fabric is one of the material for contain in this product because it material have elastic criterias that suitable for stretching. In this product have a part which is at fore arm that can prevent from any injury during training or practicing. Training by using the product can enhance quality of digging skill to the higher level and upgrade their skill performance. Moreover, players will enjoy and attract to practice and practice again.